2008
DOI: 10.1021/nl8011006
|View full text |Cite
|
Sign up to set email alerts
|

Pressure-Induced Orientation Control of the Growth of Epitaxial Silicon Nanowires

Abstract: Single crystal silicon nanowires (SiNWs) were synthesized with silane reactant using Au nanocluster-catalyzed one-dimensional growth. We have shown that under our experimental conditions, SiNWs grown epitaxially on Si(111) via the vapor-liquid-solid growth mechanism change their growth direction as a function of the total pressure. Structural characterization of a large number of samples shows that SiNWs synthesized at a total pressure of 3 mbar grow preferentially in the 111 direction, while the one at 15 mba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
101
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(113 citation statements)
references
References 46 publications
10
101
1
Order By: Relevance
“…Recently the synthesis of diameters below 10 nm has been achieved. 7 It has been demonstrated that Si NWs are rodlike structures with a bulk Si single crystalline core 8 and thus grow along well-defined crystalline directions 9,10 and follow the Si surface reconstruction criteria according to Wulff's minimum energy law, 11 thereby having a well defined shape in their cross section. 12 Due to the sp 3 nature of the Si bonding, the atoms at the surface have dangling bonds, 13 which need to be passivated in order to ensure chemical stability.…”
Section: Introductionmentioning
confidence: 99%
“…Recently the synthesis of diameters below 10 nm has been achieved. 7 It has been demonstrated that Si NWs are rodlike structures with a bulk Si single crystalline core 8 and thus grow along well-defined crystalline directions 9,10 and follow the Si surface reconstruction criteria according to Wulff's minimum energy law, 11 thereby having a well defined shape in their cross section. 12 Due to the sp 3 nature of the Si bonding, the atoms at the surface have dangling bonds, 13 which need to be passivated in order to ensure chemical stability.…”
Section: Introductionmentioning
confidence: 99%
“…24,27,28 Careful control over the growth 5 orientation is particularly important when epitaxial growth from crystalline substrates is desired. 29,30 Structural variations within NWs, such as lamellar twinning faults, have been noted in a number of seeded approaches and must be understood and controlled as they can impact the electrical and optical properties of the NWs. 31 Faults parallel and perpendicular to either the <111> or <112> growth direction of Si and Ge NWs have been shown in a number of studies [31][32][33] while more complex 10 morphological variations such as NW kinking often occurs as a result of a change in growth direction in single crystal NWs.…”
mentioning
confidence: 99%
“…With this goal in mind, we choose a low SiH 4 concentration at low pressure (also reported in Ref. [29]) for the CVD process, which corresponds with slower growth kinetics. Fig.…”
Section: Removal Of Ps Spheresmentioning
confidence: 99%